Balancing quality and well-being: a study on the impact of quality assurance measures on burnout among EFL teachers in Vietnam - Tran, Thi Thuy; Pham, Trut Thuy; Le, Thanh Thao (Frontiers in Education, 2024)
IntroductionThis qualitative study investigates the impact of quality assurance (QA) measures on the well-being and professional satisfaction of English as a Foreign Language (EFL) teachers in Vietnam, focusing on the manifestations of burnout as a direct consequence of these pressures.MethodsEmploying a phenomenological approach, semi- structured interviews were conducted with 10 Vietnamese EFL teachers from two educational institutions, exploring their experiences with QA initiatives. Thematic analysis revealed a dual burden: the intensified administrative responsibilities and heightened student expectations associated with QA processes contribute significantly to stress and burnout among teachers.Results/FindingsKey findings include the emotional exhaustion, depersonalization, and reduced personal accomplishment experienced by participants, alongside physical symptoms and mental health challenges. Teachers reported employing various coping strategies to navigate the pressures of their professional environment, highlighting their quest for professional fulfillment amidst these challenges.DiscussionThe study underscores the need for a balanced approach to QA that considers teacher well-being, advocating for policies that alleviate administrative burdens, promote work-life balance, and support professional development. Additionally, it calls for institutional prioritization of mental health resources and collaborative environments to mitigate the adverse effects of QA on teachers. The findings contribute to the discourse on QA in higher education, emphasizing the importance of supporting EFL teachers’ well-being for sustainable educational excellence.